A study on factors shaping innovative work behavior and service innovation performance in government sectors: role of digital leadership and dynamic capabilities - Lu Ren; Shuhua Deng; Lixiang Men; Azzeddine Boudouaia (Humanities & Social Sciences Communications)
Abstract Leaders greatly influence their teams’ ability to engage in innovative work behavior by creating supportive work environments. Government service innovation performance is a direct result of these behavioral changes. The goal is to achieve the highest levels of responsiveness, efficiency, and accountability in government infrastructure through cutting-edge technical solutions. This study investigates the effect of digital leadership, dynamic capabilities, and development capabilities on the leaders’ innovative work behavior and government service innovation performance in China. A questionnaire was administered to 388 leaders from different government services in China, consisting of 74 items distributed among 15 factors. Data analyses were conducted using SPSS 29, JASP, and SmartPLS 4. The findings indicate that digital leadership and dynamic capabilities do not directly enhance innovative work behavior, nor do they indirectly improve government service innovation performance through leaders’ innovative work behavior. However, digital leadership development capabilities do have a positive impact on both. Additionally, the study found that leaders’ innovative work behavior has a significant positive effect on government innovation performance. The study concludes that effective strategies should be adopted by government and leaders to promote digital leadership and its dynamic capabilities in order to improve the success of leaders’ innovative work behavior and government service innovation performance.